STRATEGI PENINGKATAN KINERJA LEMBAGA KURSUS DAN PELATIHAN (LKP) CENDANA WANGI DALAM MELAKSANAKAN PROGRAM PEMERINTAH PENDIDIKAN KECAKAPAN WIRA USAHA (PKW) - Kuswati, Teti (Jurnal Socia Akademika, 2023)
The research aims to determine the performance strategies implemented at the Cendana Wangi Course and Training Institute (LKP), in implementing the government program in the form of Entrepreneurial Skills Education (PKW). The type of research is qualitative descriptive research, data collection uses interview techniques, observation and documentation. The subject of this research is the leader of LKP Cendana Wangi. Meanwhile, the object is the performance strategy of Special and Training institutions. The data analysis method used is descriptive data analysis. The research results show that the performance strategy used is through coordination, creating work programs according to the vision and mission, preparing learning facilities and infrastructure, synchronizing Dapodik. To ensure product quality, the curriculum from directorates and institutions is made according to the SKKNI scheme and technical guidelines from the department, referring to the SKL book. LSK and LSP standards. To maintain the performance of Human Resources, by giving reminders every time there is a program, giving tasks in a friendly manner, working comfortably, safely and ensuring health. Recruitment of training participants, via E brochures, FB, IG, and WA, leaflets. Collaboration with schools, alumni, UMKM and PKK Baturetno Village.